Functionalized Multiwalled Carbon Nanotubesanticancer Drug Carriers: Synthesis, Targeting Ability and Antitumor activity - Zhong Tian; Yinfeng Shi; Min Yin; Hebei Shen; Nengqin Jia (Nano Biomedicine and Engineering, 2011)
A novel functionalized multiwalled carbon nanotubes(f-MWNTs)-anticancer drug carriers were prepared by modifying carbon nanotubes with polyethylenimine (PEI), folic acid and quantum dots for targeting and imaging cancer cells. The functionalized MWNTs exhibited good aqueous solubility, biocompatibility and high targeting ability. Water-insoluble anticancer drug Paclitaxel (PTX) were further loaded onto the f-MWNTs mainly through noncovalent π–π stacking interaction. In vitro cytotoxicity studies of f-MWNTs–PTX complexes using MTT assay exhibited a significant enhancement in the cytotoxic capability, suggesting these targeting drug carriers could facilitate intracellular delivery of anticancer drug and improve drug antitumor activity. Therefore, the highly versatile multifunctional carbon nanotubes could potentially be used for advanced drug delivery in biomedical fields.